-42=3(6+8b)+6(-3b-7)

Simple and best practice solution for -42=3(6+8b)+6(-3b-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -42=3(6+8b)+6(-3b-7) equation:


Simplifying
-42 = 3(6 + 8b) + 6(-3b + -7)
-42 = (6 * 3 + 8b * 3) + 6(-3b + -7)
-42 = (18 + 24b) + 6(-3b + -7)

Reorder the terms:
-42 = 18 + 24b + 6(-7 + -3b)
-42 = 18 + 24b + (-7 * 6 + -3b * 6)
-42 = 18 + 24b + (-42 + -18b)

Reorder the terms:
-42 = 18 + -42 + 24b + -18b

Combine like terms: 18 + -42 = -24
-42 = -24 + 24b + -18b

Combine like terms: 24b + -18b = 6b
-42 = -24 + 6b

Solving
-42 = -24 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
-42 + -6b = -24 + 6b + -6b

Combine like terms: 6b + -6b = 0
-42 + -6b = -24 + 0
-42 + -6b = -24

Add '42' to each side of the equation.
-42 + 42 + -6b = -24 + 42

Combine like terms: -42 + 42 = 0
0 + -6b = -24 + 42
-6b = -24 + 42

Combine like terms: -24 + 42 = 18
-6b = 18

Divide each side by '-6'.
b = -3

Simplifying
b = -3

See similar equations:

| 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n | | 6x+12+54=180 | | 18x+6=19x | | 2(2p-3)=36-2p | | 8(8x-1)+4(1+8x)=-4 | | -23=6x+2 | | 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 | | 17x+20=16x+20 | | 10x+1=9x+12 | | -23=6*4+2 | | x+77+x+62=45 | | 32=-6*-5+2 | | 58=-6*-7+2 | | 2x-5=4.4 |

Equations solver categories